IN -VIVO ANTI-DIARRHOEAL ACTIVITY OF METHANOL EXTRACT OF BOMBAX BUONOPOZENSE - Adamude, Fatima A.; Onyekachi, Moh Kingsley (Universal Journal of Pharmaceutical Research, 2017)
Objective: Diarrhoeal disease is responsible for mortality and morbidity, especially among children in developing countries causing a major healthcare problem. The purpose of the present study was to evaluate anti-diarrhoeal effects of methanolic extract of whole plant of Bombax buonopozense against castor oil-induced-diarrhoea model and small intestine transit model in rats. Methods: Albino wistar rats were used for estimation of anti-diarrhoeal activity. Small intestinal transit models in rats the number of droppings and the distance traveled by charcoal in intestine were measured. Loperamide (2.5 mg/kg) was used as standard drug, and it has shown significant reductions in fecal output and frequency of droppings whereas extract at the doses of 200 and 400 mg/kg reduced the castor-oil induced frequency and consistency of diarrhoea. Results: The results obtained establish the efficacy and substantiate the folklore claim as an anti- diarrhoeal agent. Conclusion: Results conclude that the leaves extract of Bombax buonopozense contains bioactive natural substances with antidiarrhoeal properties. Peer Review History: Received 8 December 2016; Revised 7 January 2017; Accepted 11 February, Available online 15 March 2017 Academic Editor: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Reviewer(s) detail: Dr. Gülay B Anadolu , Anadolu University, Eskisehir, Turkey, gbuyukko@anadolu.edu.tr Prof. Dr. Hüsniye Kayalar , Ege University, Turkey, husniyekayalar@gmail.com